Stimulation of Proteinase Activated Receptor-2 Causes Endothelial Cells to Promote Blood Coagulation In Vitro - Alm, Anna-Karin; Norström, Eva; Sundelin, Johan; Nystedt, Sverker (Thrombosis and Haemostasis, 1999)
Proteolytically activated receptors define a new subclass among the G-protein coupled receptors. Proteinase activated receptor-2 (PAR-2), the second member to be identified of this growing receptor subclass, can be activated by trypsin and trypsin-like serine proteases such as mast cell tryptase. PAR-2 is expressed in endothelial cells. Here we have studied if activation of PAR-2 changes the coagulation properties of cultured human umbilical vein endothelial cells. We show that activation of PAR-2 induces rapid and transient formation of tissue factor mRNA with a maximum level 1 hour after receptor stimulation. The increased mRNA level was accompanied by an increased tissue factor activity at the endothelial cell surface, shortening coagulation time in a standard clotting assay. The level of tissue factor activity after PAR-2 activation was comparable with the effects of thrombin receptor (PAR-1) activation although neither of the two protease receptors were as strong inducers of tissue factor as tumor necrosis factor-α.